2017
DOI: 10.1136/bmjspcare-2016-001291
|View full text |Cite
|
Sign up to set email alerts
|

Responses to assisted suicide requests: an interview study with Swiss palliative care physicians

Abstract: The Swiss model of assisted suicide gives palliative care physicians opportunities to develop roles which are compatible with each practitioner's values, but may not correspond to patients' expectations. Specific education for all palliative care professionals and more structured ways to manage communication about assisted suicide are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 41 publications
(22 reference statements)
2
38
1
7
Order By: Relevance
“…Overall, it was rare for a physician to advise a patient to make contact with a right-to-die organization. Gamondi et al 35 concluded that the Swiss model gives palliative care physicians opportunities to develop roles that are compatible with their own values, whether they correspond to the expectations of patients. They suggest that specific education for all palliative care professionals and more structured ways to manage communication concerning assisted suicide are warranted.…”
Section: Switzerland: Ambivalent Cooperation and Opposedmentioning
confidence: 99%
“…Overall, it was rare for a physician to advise a patient to make contact with a right-to-die organization. Gamondi et al 35 concluded that the Swiss model gives palliative care physicians opportunities to develop roles that are compatible with their own values, whether they correspond to the expectations of patients. They suggest that specific education for all palliative care professionals and more structured ways to manage communication concerning assisted suicide are warranted.…”
Section: Switzerland: Ambivalent Cooperation and Opposedmentioning
confidence: 99%
“…20,21 There is no federal law regulating protocols for assisted suicide provision in Switzerland, although two cantons (Vaud and Neuchatel) have recently enacted legislation regulating assisted suicide in public institutions. 8 Switzerland constitutes a unique model of assisted suicide, the so-called ''civil model.'' 22,23 Assisted suicide mainly occurs at the patient's home with the assistance of right-to-die associations as few health care institutions permit it.…”
Section: Assisted Suicide In Switzerlandmentioning
confidence: 99%
“…The assigned volunteer evaluates the patient's mental capacity before ingestion and assists during selfingestion of the drug. 8 Crucial criteria to access assisted suicide involving right-to-die associations are the fact that the patient's suffering should be unbearable and without further options of care. Previous studies show that in Switzerland, family involvement in assisted suicide is common with discussions during preparation restricted to a small circle of people.…”
Section: Assisted Suicide In Switzerlandmentioning
confidence: 99%
“…Lack of time to properly evaluate suffering and provide the standard of care that palliative care providers feel patients need and deserve puts such providers at risk of experiencing moral distress 28. Regarding non-abandonment, a similar concern was also documented among Swiss palliative care physicians, who found it difficult to accompany patients in decision-making about assisted suicide while honouring palliative care principles that do not support this practice 11. Interestingly, the theme of non-abandonment figures among the reasons that US physicians provide for supporting the decriminalisation of euthanasia 29.…”
Section: Discussionmentioning
confidence: 96%
“…A study of hospice policies regarding PAS in the states of Oregon and Washington revealed that although hospices do not participate directly in hastened deaths, there were inconsistencies and dilemmas regarding their role in providing information, in participating in the decision-making process and in accompanying patients 9 10. Finally, according to a qualitative study from Switzerland, where requests for assisted suicide are managed by right-to-die societies in parallel to the healthcare system, palliative care providers reported advising patients who made requests, but most refused to write lethal prescriptions 11. The authors report that participants struggled to reconcile their commitment to palliative care principles with patients’ wishes to exercise their autonomy 11…”
Section: Introductionmentioning
confidence: 99%